Postnatal maturation of microglia is associated with alternative activation and activated TGFβ signaling. Issue 8 (25th March 2018) - Attaai, Abdelraheim; Neidert, Nicolas; von Ehr, Alexander; Potru, Phani Sankar; Zöller, Tanja; Spittau, Björn
Abstract: Microglia are involved in a widespread set of physiological and pathological processes and further play important roles during neurodevelopmental events. Postnatal maturation of microglia has been associated with the establishment of microglia‐specific gene expression patterns. The mechanisms governing microglia maturation are only partially understood but Tgfβ1 has been suggested to be one important mediator. In the present study, we demonstrate that early postnatal microglia maturation is associated with alternative microglia activation, increased engulfment of apoptotic cells as well as activated microglial Tgfβ signaling. Interestingly, microglial Tgfβ signaling preceded the induction of the microglia‐specific gene expression indicating the importance of Tgfβ1 for postnatal microglia maturation. Moreover, we provide evidence that Tgfβ1 is expressed by neurons in postnatal and adult brains defining neuron‐microglia communication via Tgfβ1 as an important event. Finally, we introduce the recently identified microglia marker Tmem119 as a direct Tgfβ1‐Smad2 target gene. Taken together, the data presented here further increase the understanding of Tgfβ1‐mediated effects in microglia and place emphasis on the importance of Tgfβ1 for microglia maturation and maintenance. Main Points: Activated microglial Tgfβ signalling precedes the induction of microglia‐specific gene expression patterns. Tgfβ1 expression in postnatal and adult NeuN + neurons. Identification of Tmem119 as a direct Tgfβ1 target gene.